Development, Characterization, and Stability Evaluation of the Anti-Cellulite Emgel Containing Herbal Extracts and Essential Oils - Ngamrayu Ngamdokmai; Kornkanok Ingkaninan; Nattiya Chaichamnong; Krongkarn Chootip; Nitra Neungchamnong; Neti Waranuch (MDPI AG, 2021)
Recently, the herbal compress was successfully developed and applied for cellulite treatment. The aim of this study was to formulate a more convenient dosage form of herbal application from the original formula. In addition, we aimed to characterize and evaluate the stability of the developed dosage form. A gelled emulsion, or an "emgel," incorporated with 0.1 wt% tea and coffee extracts (1:1 ratio) plus 5 wt% essential oils (mixed oil) was prepared. The caffeine content in the finished product obtained from tea and coffee extracts analyzed by HPLC was 48.1 ± 2.3 µg/g. The bio-active marker monoterpenes of mixed oil characterized by headspace GCMS were camphene 50.8 ± 1.8 µg/mg, camphor 251.0 ± 3.2 µg/mg, 3-carene 46.7 ± 1.8 µg/mg, α-citral 75.0 ± 2.1 µg/mg, β-citral 65.6 ± 1.3 µg/mg, limonene 36.8 ± 6.7 µg/mg, myrcene 53.3 ± 4.5 µg/mg, α-pinene 85.2 ± 0.6 µg/mg, β-pinene 88.4 ± 1.1 µg/mg, and terpinene-4-ol 104.3 ± 2.6 µg/mg. The stability study was carried out over a period of 3 months at 4, 25, and 50 °C. The caffeine content showed no significant changes and passed the acceptance criteria of ≥80% at all tested temperatures. However, monoterpenes showed their stability for only 2 months at 50 °C. Therefore, the shelf-life of the emgel was, consequently, calculated to be 31 months using the Q10 method. Thus, the anti-cellulite emgel was successfully formulated. The characterization methods and stability evaluation for caffeine and monoterpenes in an emgel matrix were also successfully developed and validated.